Method for measuring content of unstable end groups in fluorine-containing polymer PFA
The integrated area of characteristic absorption peaks of unstable end groups in PFA was measured by infrared spectrometry and the molar content was calculated, which solved the problem of long measurement time and low accuracy in the prior art, and achieved fast and accurate quantitative analysis of unstable end groups.
Patent Information
- Application Number
- CN202311099401.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to measure the content of unstable end groups in fluoropolymer PFA in rapid and accurate quantification, resulting in long and cumbersome testing time, poor data reproducibility, and inability to distinguish different types of unstable end groups.
Infrared spectroscopy was used to measure the molar content of the -CF2-CF2 group in PFA, and the molar content of the unstable end groups was calculated by the characteristic absorption peak integral area, and the calculation was performed using the formula n% terminal = 0.0025×(S-terminal/STFE)×n% TFE.
It realizes rapid and stable measurement of the content of unstable end groups in PFA, with good data reproducibility and high accuracy of results, and is suitable for quality control in the polymerization and post-processing stages of high-quality PFA.
Smart Images

Figure BDA0004423297560000024 
Figure BDA0004423297560000034 
Figure BDA0004423297560000035
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical analysis, and in particular to a quantitative measurement and analysis method for unstable end groups in a fluorine-containing polymer PFA. Background Art
[0002] PFA refers to a copolymer of a small amount of perfluoropropyl perfluorovinyl ether (PPVE) and polytetrafluoroethylene (PTFE). By introducing a small amount of PPVE into PTFE, modified groups are introduced to give the material excellent creep resistance and compressive strength properties.
[0003] In the PFA polymerization process, due to the use of inorganic peroxides (such as potassium persulfate K2S2O8, ammonium persulfate (NH4)2S2O8 initiators in the chain initiation and termination stages, a large number of carboxylic acid end groups can be generated, or the vinyl bonds in the fluoropolymer molecular chain itself are oxidized to carboxyl groups, resulting in unstable end groups such as carboxyl groups in the fluoropolymer molecular chain. Peroxide initiators can also lead to the generation of fluoroacyl -COF, which is unstable in water and generates -COOH and hydrofluoric acid after decomposition. At the processing temperature of fluoropolymers, -COOH decomposes into CO2 and -CF=CF-, the latter of which can be oxidized to -COOH, generating corrosive gases. During the processing process, bubbles are generated and remain in the product, which greatly affects the performance, appearance and use of fluoropolymers, and brings huge economic losses in industrial production. Therefore, it is necessary to have a clear understanding of the types and contents of end groups contained in fluoropolymers to provide accurate key data for the process of de-end grouping.
[0004] Due to the strong solvent resistance of PFA, the material is difficult to dissolve in any solvent, so the qualitative and quantitative testing of the extremely small amount of unstable functional groups contained in the material cannot be carried out by mass spectrometry, nuclear magnetic resonance, etc. Among the existing instrumental analysis methods, only infrared spectroscopy can accurately characterize functional groups, but it is difficult to obtain standard samples with known contents, so quantitative calculations cannot be performed.
[0005] In the traditional analysis method, PFA materials are generally soaked in ultrapure water for a long time, and the F ion concentration in the soaking liquid is tested to reversely deduce and estimate the unstable end group content in PFA. This method takes a long time to test, and one test takes more than 12 days. It is extremely cumbersome, has many interference factors, poor data reproducibility, and cannot distinguish the types of unstable end groups. Therefore, it is not suitable for quality control and process adjustment of high-quality PFA polymerization and post-processing stages. Therefore, it is necessary to propose a quantitative analysis method for trace unstable end groups in PFA polymer segments. Summary of the invention
[0006] In order to solve one of the above-mentioned technical problems existing in the prior art, the present invention provides a method for quickly and stably measuring the content of trace unstable end groups in PFA polymer segments, with good data reproducibility and high result accuracy, which can realize reliable quality control of high-quality PFA polymerization and post-processing stages.
[0007] The technical solution of the present invention is as follows:
[0008] A method for measuring the content of unstable end groups in a fluorinated polymer PFA comprises the following steps:
[0009] S1. Measure the molar content n% of -CF2-CF2 groups in the sample to be tested TFE ;
[0010] S2. Using infrared spectroscopy to measure the characteristic absorption peak integral area S of the -CF2-CF2 group in the sample to be tested TFE , and the infrared characteristic absorption peak integral area S of any unstable end group in the sample to be tested 端 Or the sum of the integrated areas of the infrared characteristic absorption peaks of various unstable end groups S 端-总 ;
[0011] S3. Calculate the molar content n% of any unstable end group in the sample to be tested by the following formula: 端 Or the total molar content of various unstable end groups n% 端-总 :
[0012] n% 端 =0.0025×(S 端 / S TFE )×n% TFE
[0013] n% 端-总 =0.0025×(S 端-总 / S TFE )×n% TFE .
[0014] In some embodiments, step S1 comprises:
[0015] S(1). Measurement of N known TFE monomer molar contents of standard PFA by infrared spectroscopy at (2363±10) cm -1 and (993±10)cm -1 The integrated area of the absorption peak at the wave number A 2363 and A 993 ,get and The relationship curve between and fitting is obtained
[0016] S(2). Infrared spectroscopy was used to measure the sample at (2363±10)cm -1 The absorption peak integrated area S at the wave number 2363 and (993±10)cm -1 The absorption peak integrated area S at the wave number 993 ;
[0017] S (3) Calculate the molar content of -CF2-CF2 groups in the sample to be tested by the following formula n% TFE :
[0018]
[0019] Among them, n 标 % TFE Indicates the molar content of TFE monomer in standard PFA,
[0020] n 标 % PPVE Indicates the molar content of PPVE monomer in the standard PFA,
[0021] K p Indicates that the -O-CF3 group in the standard PFA is at (993±10)cm -1 The sensitivity of
[0022] K0 represents the -CF2-CF2 group in the standard PFA at (2363±10)cm -1 The sensitivity of the
[0023] In some embodiments, in step S(1), N≥3. In some embodiments, in step S(1), 4≤N≤10, for example, N can be 4, 5, 6, 7, 8, 9 or 10.
[0024] In some embodiments, the molar percentage of TFE monomer in the standard PFA is 90-99%.
[0025] In some embodiments, the molar percentage of PPVE monomer in the standard PFA is 1-10%.
[0026] In some embodiments, The ratio of is between 5 and 6. In some embodiments, The ratio of is between 5.5 and 5.6. In some embodiments,
[0027] In some embodiments, in step S2, S TFE The -CF2-CF2 group in the sample to be tested is (2363±10)cm -1 The absorption peak integrated area S at the wave number2363 .
[0028] In some embodiments, the unstable end groups include one or more of -COF, -COOH, and -CF=CF2.
[0029] The method of the present invention can test the content of each unstable end group of the PFA polymer segment separately, and can also test the total content of multiple unstable end groups of the PFA polymer segment. For example, when it is necessary to measure the content of any one of the unstable end groups of -COF, -COOH and -CF=CF2, S 端 =S -COF , or S 端 =S -COOH , or S 端 =S -COOH ; When it is necessary to measure the total content of any two or three unstable end groups among -COF, -COOH and -CF=CF2, S 端-总 =S -COF +S -COOH +S -COOH ; Among them, S -COF Indicates that the -COF in the sample to be tested is (1882±10)cm -1 The integrated area of the characteristic absorption peak at the wave number, S -COOH Indicates that -COOH in the sample to be tested is at (1812±10)cm -1 and (1769±10)cm -1 The integrated area of the characteristic absorption peak at the wave number, S -CF=CF2 Indicates that -CF=CF2 in the sample to be tested is at (1793±10)cm -1 The integrated area of the characteristic absorption peak at the wave number.
[0030] In some embodiments, the method comprises:
[0031] The sample to be tested was pressed into a tablet and placed in an infrared spectrometer at 400-4000cm -1 Scan within the wave number range to obtain the infrared spectrum;
[0032] The molar content n% of the -CF2-CF2 group in the sample to be tested is calculated according to the following formula: TFE :
[0033]
[0034] The total molar content n% of the unstable end groups in the sample to be tested is calculated according to the following formula 端-总 :
[0035]
[0036] Among them, S 2363 Indicates (2363±10)cm obtained according to the infrared spectrum -1 The integrated area of the absorption peak at the wave number;
[0037] S 993 Indicates (993±10)cm obtained according to the infrared spectrum -1 The integrated area of the absorption peak at the wave number;
[0038] S 1882 Indicates (1882±10)cm obtained according to the infrared spectrum -1 The integrated area of the absorption peak at the wave number;
[0039] S 1812 Indicates (1812±10)cm obtained according to the infrared spectrum -1 The integrated area of the absorption peak at the wave number;
[0040] S 1769 Indicates (1769±10)cm obtained according to the infrared spectrum -1 The integrated area of the absorption peak at the wave number;
[0041] S 1793 It represents (1793±10)cm obtained according to the infrared spectrum. -1 The integrated area of the absorption peak at that wave number.
[0042] In some embodiments, the sample to be tested is in powder or granular form.
[0043] In some embodiments, the powdered sample is compressed into tablets through a mold at a pressure of 3.5-6.5 MPa.
[0044] In some embodiments, the granular sample to be tested is pressed into tablets by a hot press at a temperature of 260-300°C.
[0045] In some embodiments, a hot press is used to press the granular sample to be tested into a surface greater than or equal to 0.25 cm 2 Samples of .
[0046] In some embodiments, the method further comprises the steps of washing and drying the sample to be tested before tableting.
[0047] In some embodiments, the sample is washed with water.
[0048] In some specific embodiments, the drying temperature is 65-100° C., and the drying time is 2-5 hours.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] The testing method provided by the present invention is short in time, high in efficiency, less affected by external factors such as the environment, and has good data reproducibility. It can accurately reflect the content of unstable end groups such as -COF, -COOH, and -CF=CF2 separately and separately, and can also simultaneously test the total content of unstable end groups such as -COF, -COOH, and -CF=CF2. It can provide timely and accurate key data for post-production processing, and realize reliable quality control of high-quality PFA polymerization and post-processing stages. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 It shows that PFA has a range of 400 to 4000 cm -1 Infrared spectra over a range of wavenumbers.
[0052] Figure 2 The specific embodiment of the present invention is shown in FIG. 2363 / A 993 is the horizontal axis, with n% TFE / n% PPVE The vertical axis is the fitted curve.
[0053] Figure 3 The infrared spectra of samples a1 and b1 in a specific embodiment of the present invention are shown. DETAILED DESCRIPTION
[0054] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention.
[0055] The method for measuring the unstable end group content in the fluorine-containing polymer PFA of the present invention can be divided into three parts: sample preparation, infrared spectrum data collection, and calculation. Specifically, the PFA sample to be tested is pretreated by water washing, drying, film pressing / sheet pressing, etc. to prepare a sample with uniform thickness, light transmittance, no surface damage, and no bubbles, and specific parameters are set on the infrared spectrometer to ensure the accuracy of the collected information. After the spectrum detection is completed, characteristic peak calculation is performed.
[0056] (I) Sample preparation
[0057] The PFA sample to be tested in the present invention can be in powder or granular form. The methods for pretreatment of samples of different shapes and preparation of samples are as follows:
[0058] 1.1 PFA pretreatment of unformed materials such as powder
[0059] (1) Preparation before testing:
[0060] The samples were dried at 85-100°C for 2-3 h to remove trace moisture from the materials.
[0061] (2) Sample preparation:
[0062] Weigh 150±5mg of sample accurately, put it into a Φ12.95mm stainless steel cylindrical mold, press it under 5±1.5MPa pressure, and keep it at room temperature for 1min. After demoulding, observe that the thickness of the sample is uniform and transparent, and there is no damage or bubble on the surface. The standard sample is prepared and put into use.
[0063] 1.2 PFA pretreatment of pellets and other forming states
[0064] (1) Preparation before testing:
[0065] Take 0.5-3g of sample and put it into a clean PP bottle. Mix it in the ratio of sample: ultrapure water = 1g: 100mL, then ultrasonicate for 1min. Take out the sample and put it into a clean PP bottle. Repeat this operation twice to wash away the unreacted impurities remaining on the surface of the sample. Take out the sample and dry it at 65-80℃ for 2-5h until the sample is completely dry.
[0066] (2) Sample preparation:
[0067] Select the thickness ring with a specification of 500 μm, put the disposable aluminum foil into the hot press, add a complete sample (10-50 mg), set the hot pressing film temperature to 280°C, stop heating after hot pressing for 15-30 minutes, wait until the temperature drops below 70°C, demould, and observe whether the surface area of the sample is greater than or equal to 0.25 cm 2 If the pellets are too small and less than 10 mg, 2-5 samples can be pressed in this way, and then the pressed samples can be stacked and the hot pressing operation can be repeated to produce pellets with a surface area greater than or equal to 0.25 cm 2 Samples of .
[0068] (II) Infrared spectral data collection
[0069] 2.1 Test methods and parameters
[0070] Set the infrared spectrometer parameters as follows:
[0071] Wavelength range: 400~4000cm -1 ;
[0072] Resolution: 4cm -1 ;
[0073] Number of collections: 32
[0074] Acquisition mode: Transmission mode (TR)
[0075] 2.2 Spectral peak attribution: After signal acquisition, the spectral peaks are processed and qualitatively attributed (such as Figure 1 (shown)
[0076] Peak position 2363cm -1 Nearby (2363±10cm -1 ): -CF2-CF2
[0077] Peak position 1882cm -1 Nearby (1882±10cm -1 ): -COF end group
[0078] Peak position 1812cm -1 Nearby (1812±10cm -1 ): -COOH terminal group (out-of-plane bending vibration)
[0079] Peak position 1793cm -1 Nearby (1793±10cm -1 ): -CF = CF2 terminal group
[0080] Peak position 1769cm -1 Nearby (1769±10cm -1 ): -COOH terminal group (simple vibration)
[0081] Peak position 993cm -1 Nearby (993±10cm -1 ): Bending vibration of non-main-chain CF bonds directly connected to O atoms in PPVE
[0082] Peak position 936cm -1 Nearby (936±10cm -1 ): deformation vibration of the main chain CF bond in the main structural unit of PTFE
[0083] Among the above characteristic absorption peaks, there are a large number of stable -CF2-CF2 in PFA and a small amount of -O-CF3 groups in PPVE, as well as trace or trace amounts of 1760~1900cm -1 Unstable end groups within the range.
[0084] (III) Points calculation
[0085] 3.1 Calculation of PTFE content in PFA
[0086] Since PFA is mainly formed by the polymerization of PTFE and PPVE, it is believed that the characteristic peak areas of the two monomers TFE and PPVE have the following relationship:
[0087] K0×(n% TFE / A 2363 )=Kp ×(n% PPVE / A 993 ) (1)
[0088] Among them, K0 is -CF2-CF2 group at 2363cm -1 Sensitivity at K p The -O-CF3 group is at 993cm -1 Sensitivity.
[0089] The present invention calculates K0 and K by fitting the PFA infrared characteristic peak area integral with known PPVE content. p The specific method is as follows:
[0090] The sample was dried at 100°C for 2h, and 150mg of PFA powder standard sample (PPVE molar percentages were 5.37%, 2.96%, and 1.09%, respectively) was accurately weighed and placed in a Φ12.95mm stainless steel column mold, and pressed under 5MPa pressure, and kept at room temperature for 1min. After demolding, the sample was observed to be uniform in thickness and translucent, with no damage or bubbles on the surface. The standard sample was prepared and put into use. The sample was placed in an infrared spectrometer and scanned in TR mode with a scanning range of 400-4000cm -1 , scanning times 32 times, resolution 4cm -1 The infrared spectrum obtained was analyzed and the 2363cm -1 The integrated area of the absorption peak at the wave number A 2363 , and 993cm -1 The integrated area of the absorption peak at the wave number A 993 , the test results are shown in Table 1 below.
[0091] Table 1 Standard sample infrared spectrum test data
[0092] <![CDATA[n% PPVE ]]> <![CDATA[n% TFE ]]> <![CDATA[A 993 ]]> <![CDATA[A 2363 ]]> <![CDATA[A 2363 / A 993 ]]> <![CDATA[n% TFE / n% PPVE ]]> 5.37 94.63 12.333 35.326 2.864 17.622 2.96 97.04 8.624 53.992 6.261 32.784 1.09 98.91 2.339 37.969 16.233 90.743
[0093] According to the above formula (1), we can know that: K p / K0=(n% TFE / n% PPVE ) / (A 2363 / A 993 );
[0094] For Table 1 A 2363 / A 993 and n% TFE / n% PPVE The data were fitted at the origin, such as Figure 2 As shown, we can get K p / K0=5.5603
[0095] Thus, the approximate molar percentage of TFE monomer in PFA can be deduced as n% TFE :
[0096] n% TFE =5.5603×n% PPVE ×(A 2363 / A 993 )=5.5603×(1-n% TFE )×(A 2363 / A 993 ) (2)
[0097] Among them, n% PTFE To ignore the unstable group content, the molar percentage of TFE contained in PFA; n% PPVE is the molar percentage of PPVE; A 2363 2363cm -1 The peak area integration at A 993 993cm -1 The peak area integration at .
[0098] 3.2 Calculation of unstable end group content in PFA
[0099] PFA standard samples with known unstable end group content are not easy to obtain, and there are bound to be deviations in the sample preparation process. Factors that affect the optical path of infrared spectra, such as sample thickness and density, will greatly affect data reproducibility. The calculated values of unstable end group content of the same sample may even differ by more than 10 times. Therefore, the area ratio method is used to eliminate sample errors.
[0100] Since the PTFE content in PFA is very high, the TFE monomer concentration is close to 100%, and the -CF2-CF2 group is at 2363cm -1 The peak area is stable and not easy to be flat. Therefore, by integrating the infrared characteristic peak area, the approximate molar percentage of the unstable end group in PFA can be fitted and calculated:
[0101] K0×(n% PTFE ) / S 2363 =K1×(n% -COF ) / S -COF , where S -COF =S 1882 (3)
[0102] K0×(n% PTFE ) / S 2363 =K2×(n% -COOH ) / S -COOH , where S -COOH =S 1812 +S 1769 (4)
[0103] K0×(n% PTFE ) / S 2363 =K3×(n% -CF=CF2 ) / S -CF=CF2 , where S -CF=CF2 =S 1793 (5)
[0104] The total number of unstable end groups is n% 端-总 =n% -COF +n% -COOH +n% -CF=CF2 (10)
[0105] The total area of unstable end groups is S 端-总 =S -COF +S -COOH +S -CF=CF2 (11)
[0106] Among them, K0 is -CF2-CF2 group at 2363cm -1 The sensitivity of K1, K2 and K3 are -COF, -COOH and -CF=CF2 terminal groups at 1882cm -1 、1812cm -1 +1769cm -1 、1793cm -1 Peak sensitivity at S 1812 , S 1769 , S 1793 , S 1882 are the peak area integrals at the corresponding wavenumbers. It should be noted that in formula (5), the -CF=CF2 group is at 1793 cm -1 The peak area integral S 1793 The 1812cm adjacent to it needs to be removed during calculation. -1 The peak area integration at .
[0107] Since the content of unstable end groups such as -COF, -COOH, and -CF=CF2 in PFA is extremely low (proven by F ion leaching experiments, their total content should be at the ppm or ppb level), standard samples with accurate end group content are not easy to obtain. Therefore, this application uniformly considers the sensitivity coefficients of such unstable end groups to be equal (i.e., K1=K2=K3), and their sensitivity coefficients are uniformly recorded as k 端 , due to its extremely low content, the error caused can be ignored.
[0108] Determine K0 and k by experiment 端 The specific method is as follows:
[0109] Take 3g of a sample with a PPVE molar percentage of 5.37n% and put it into a clean PP bottle. Add 300ml of ultrapure water and mix it. Ultrasonicate for 1min, remove the sample and put it into a clean PP bottle. Repeat this operation twice to wash away the unreacted impurities remaining on the surface of the sample. Remove the sample and dry it at 65-80℃ for 5h until the sample is completely dry. Divide the washed sample into two parts, a and b. Among them, a can remove some unstable end groups such as -COF, -COOH, and -CF=CF2 after fluorination treatment such as soaking in hot alkali solution and contacting with fluorine gas. b is not treated in any way.
[0110] Take 3 pellets (uniform weight, about 18 mg) from a and b respectively, select a thickness ring with a specification of 500 μm, put a disposable aluminum foil into the hot press, add a complete sample, set the hot pressing film temperature to 280°C, stop heating after hot pressing for 20 minutes, wait until the temperature drops below 70°C, demould, and measure the surface area of the sample, which is about 0.5 cm 2 , uniform thickness and light-transmissive, with no damage or bubbles on the surface. In this way, 6 samples were obtained, namely a1, a2, a3, b1, b2, and b3.
[0111] The infrared test of the sample was carried out according to the test method and parameters described in 2.1. The infrared spectrum obtained was analyzed and the 1882cm -1 、1812cm -1 、1769cm -1 、1793cm -1 The integrated areas of the absorption peaks at the wave numbers are S 1882 , S 1812 , S 1769 , S 1793 , measuring 2363cm -1 The absorption peak integrated area S at the wave number 2363 The test results are shown in Table 2. Among them, the infrared spectrum target peak comparison of sample a1 and sample b1 is shown in Figure 3 .
[0112] Table 2 Fluorination treatment rear end absorption peak integration results
[0113]
[0114] 1g of the remaining samples a and b were taken respectively, and soaked in ultrapure water at 85°C for 12 days, and the amount of F-leached therein was tested by ion chromatography. Among them, the amount of F-leached in sample a was 83.74ppm, and the amount of F-leached in sample b was 21.31ppm, that is, after being soaked in hot alkali solution and contacted with fluorine gas, the unstable end groups were reduced by 84.74-21.31=62.43ppm.
[0115] From formulas (3) to (5) and (10) to (11), we can get:
[0116] K0 / k 端 =(n% 端-总 ) / [(S 端-总 / S 2363 )×n% PTFE ]
[0117] =(62.43×10 -6 ) / [(0.056391-0.029999)×94.63%]
[0118] =0.0025.
[0119] It follows that:
[0120] K0 / k 端 =0.0025 (6)
[0121] n% -COF =0.0025×(S -COF / S 2363 )×n% PTFE (7)
[0122] n% -COOH =0.0025×(S -COOH / S 2363 )×n% PTFE (8)
[0123] n% -CF=CF2 =0.0025×(S -CF=CF2 / S 2363 )×n% PTFE (9)
[0124] That is: n% 端-总 =0.0025×(S 端-总 / S 2363 )×n% PTFE (12)
[0125] Example 1
[0126] 1. Test of PPVE content in PFA powder
[0127] The PFA sample was dried at 100℃ for 2h, 150mg of PFA powder sample was accurately weighed and loaded into a Φ12.95mm stainless steel column mold, and pressed under 5MPa pressure, and kept at room temperature for 1min. After demolding, the sample was observed to be uniform in thickness and transparent, with no damage or bubbles on the surface. The standard sample was prepared and put into use. The sample was placed in the infrared spectrometer and scanned in TR mode with a scanning range of 400-4000cm -1, scanning times 32 times, resolution 4cm -1 The infrared spectrum obtained was analyzed and the 2363cm -1 The integrated area of the absorption peak at the wave number A 2363 =30.548, and 993cm -1 The integrated area of the absorption peak at the wave number A 993 =4.052.
[0128] According to formula (2):
[0129] n% TFE =5.5603×(1-n% TFE )×(30.548 / 4.052), we can get n% TFE =97.67%
[0130] n% PPVE =1-n% TFE =2.33%
[0131] 2. Test of unstable end group content in PFA powder
[0132] The infrared spectrum obtained in step 1 is analyzed. According to step 1, the PPVE content in the sample is 2.33%, the TFE content is 97.67%, and the A 2363 =30.548, measured 1882cm -1 、1812cm -1 、1769cm -1 、1793cm -1 The integrated areas of the absorption peaks at the wave numbers are S 1882 =0.285, S 1812 =1.506, S 1769 =0.034, S 1793 =0.935, substituting into formula (12) we get:
[0133] n% 端-总 =0.0025×(S 端-总 / S 2363 )×n% PTFE =0.0025×(2.76 / 30.548)×97.67%=0.022%
[0134] Embodiment 2:
[0135] 1. Test of PPVE content in PFA pellets
[0136] Take 1g of PFA pellet sample and put it into a clean PP bottle. Add 100ml of ultrapure water and mix it. Ultrasonicate for 1min, remove the sample and put it into a clean PP bottle. Repeat this operation twice to wash away the unreacted impurities remaining on the surface of the sample. Remove the sample and dry it at 75℃ for 5h until the sample is completely dry. Take 1 pellet (weighing about 13mg), select a thickness ring with a specification of 500 microns, put a disposable aluminum foil into the hot press, add 1 complete sample, set the hot pressing film temperature to 280℃, stop heating after hot pressing for 20min, wait until the temperature drops below 70℃, demould, and measure the surface area of the sample, which is about 0.4cm 2 , uniform thickness and light-transmissive, with no damage or bubbles on the surface.
[0137] Place the sample into the infrared spectrometer and scan in TR mode with a scanning range of 400-4000cm -1 , scanning times 32 times, resolution 4cm -1 The infrared spectrum obtained was analyzed and the 2363cm -1 The integrated area of the absorption peak at the wave number A 2363 =24.119, and 993cm -1 The integrated area of the absorption peak at the wave number A 993 =3.920.
[0138] According to formula (2):
[0139] n% TFE =5.5603×(1-n% TFE )×(24.119 / 3.920), we can get n% TFE =97.16%
[0140] n% PPVE =1-n% TFE =2.84%
[0141] 2. Test of unstable end group content in PFA pellets
[0142] The infrared spectrum obtained in step 1 is analyzed. According to step 1, the PPVE content in the sample is 2.84%, the TFE content is 97.16%, and the A 2363 =24.119, measuring 1882cm -1 、1812cm -1 、1769cm -1 、1793cm -1 The integrated areas of the absorption peaks at the wave numbers are S 1882 =0.155, S 1812 =0.810, S 1769 =0.00701, S 1793=0.506, substituting into formula (12) we get:
[0143] n% 端-总 =0.0025×(S 端-总 / S 2363 )×n% PTFE =0.0025×(1.478 / 24.119)×97.16%=0.015%
[0144] Embodiment 3:
[0145] This embodiment provides a method for detecting the content of unstable end groups in PFA powder, which is different from the embodiment 1 only in that: 145 mg of sample is accurately weighed, pressed into tablets under a pressure of 6.5 MPa, and kept at room temperature for 1 minute. The sample is placed in an infrared spectrometer and scanned in TR mode with a scanning range of 400-4000 cm -1 , scanning times 32 times, resolution 4cm -1 The infrared spectrum obtained was analyzed and the 2363cm -1 The integrated area of the absorption peak at the wave number A 2363 =29.564, and 993cm -1 The integrated area of the absorption peak at the wave number A 993 =3.956. Measurement 1882cm -1 、1812cm -1 、1769cm -1 、1793cm -1 The integrated areas of the absorption peaks at the wave numbers are S 1882 =0.274, S 1812 =1.456, S 1769 =0.032, S 1793 =0.903.
[0146] Substituting into formula (2):
[0147] n% TFE =5.5603×(1-n% TFE )×(29.564 / 3.956), we can get n% TFE =97.65%
[0148] n% PPVE =1-n% TFE =2.35%
[0149] Substituting into formula (12) we can get:
[0150] n% 端-总 =0.0025×(S 端-总 / S 2363 )×n% PTFE=0.0025×(2.665 / 29.564)×97.65%=0.022%
[0151] Comparison of the calculation results of Example 1 and Example 3, n% TFE and n% PPVE Deviation is 0.02%, unsaturated end group n% 端-总 The deviation is 0.00%, which shows that the method of this patent has good repeatability and can also verify the reliability of this method.
[0152] Embodiment 4:
[0153] This embodiment provides a method for detecting the content of unstable end groups in PFA pellets. The difference from the embodiment 2 is that: 2 PFA pellets (about 8-9 mg) are taken respectively, and after being pressed into 2 samples in 2 times, the two samples are stacked up and pressed into 1 sample in the same way. After demolding, the surface area of the sample is measured to be about 0.7 cm 2 The sample is placed in the infrared spectrometer and scanned in TR mode with a scanning range of 400-4000cm -1 , scanning times 32 times, resolution 4cm -1 The infrared spectrum obtained was analyzed and the 2363cm -1 The integrated area of the absorption peak at the wave number A 2363 =39.275, and 993cm -1 The integrated area of the absorption peak at the wave number A 993 =6.337. Measurement 1882cm -1 、1812cm -1 、1769cm -1 、1793cm -1 The integrated areas of the absorption peaks at the wave numbers are S 1882 =0.253, S 1812 =1.322, S 1769 =0.014, S 1793 =0.829.
[0154] Substituting into formula (2):
[0155] n% TFE =5.5603×(1-n% TFE )×(39.275 / 6.337), we can get n% TFE =97.18%
[0156] n% PPVE =1-n% TFE =2.82%
[0157] Substituting into formula (12) we can get:
[0158] n% 端-总 =0.0025×(S 端-总 / S 2363 )×n% PTFE =0.0025×(2.418 / 39.275)×97.18%=0.015%
[0159] Comparison of the calculation results of Example 2 and Example 4, n% TFE and n% PPVE Deviation is 0.02%, unsaturated end group n% 端-总 The deviation is 0.00%, which shows that the method of this patent has good repeatability and can also confirm the reliability of this method.
[0160] Embodiment 5:
[0161] This embodiment provides a method for detecting the content of unstable end groups in PFA pellets. The difference from embodiment 2 is that: the heating is stopped after hot pressing for 15 minutes at 280°C, and the surface area of the sample is measured after demoulding, which is about 0.5 cm 2 The sample is placed in the infrared spectrometer and scanned in TR mode with a scanning range of 400-4000cm -1 , scanning times 32 times, resolution 4cm -1 The infrared spectrum obtained was analyzed and the 2363cm -1 The integrated area of the absorption peak at the wave number A 2363 =27.454, and 993cm -1 The integrated area of the absorption peak at the wave number A 993 =4.462. Measured 1882cm -1 、1812cm -1 、1769cm -1 、1793cm -1 The integrated areas of the absorption peaks at the wave numbers are S 1882 =0.179, S 1812 =0.932, S 1769 =0.007, S 1793 =0.571.
[0162] Substituting into formula (2):
[0163] n% TFE =5.5603×(1-n% TFE )×(27.454 / 4.462), we can get n% TFE =97.16%
[0164] n% PPVE =1-n% TFE=2.84%
[0165] Substituting into formula (12) we can get:
[0166] n% 端-总 =0.0025×(S 端-总 / S 2363 )×n% PTFE =0.0025×(1.689 / 27.454)×97.16%=0.015%
[0167] Comparison of the calculation results of Example 2 and Example 5, n% TFE and n% PPVE Deviation is 0.00%, unsaturated end group n% 端-总 The deviation is 0.00%.
[0168] Embodiment 6:
[0169] This embodiment provides a method for detecting the content of unstable end groups in PFA pellets. The difference from the embodiment 2 is that the heating is stopped after hot pressing for 30 minutes at 280°C, and the surface area of the sample is measured after demoulding, which is about 0.5 cm 2 The sample is placed in the infrared spectrometer and scanned in TR mode with a scanning range of 400-4000cm -1 , scanning times 32 times, resolution 4cm -1 The infrared spectrum obtained was analyzed and the 2363cm -1 The integrated area of the absorption peak at the wave number A 2363 =23.384, and 993cm -1 The integrated area of the absorption peak at the wave number A 993 =3.773. Measurement 1882cm -1 、1812cm -1 、1769cm -1 、1793cm -1 The integrated areas of the absorption peaks at the wave numbers are S 1882 =0.153, S 1812 =0.776, S 1769 =0.007, S 1793 =0.504.
[0170] Substituting into formula (2):
[0171] n% TFE =5.5603×(1-n% TFE )×(23.384 / 3.773), we can get n% TFE =97.18%
[0172] n%PPVE =1-n% TFE =2.84%
[0173] Substituting into formula (12) we can get:
[0174] n% 端-总 =0.0025×(S 端-总 / S 2363 )×n% PTFE =0.0025×(1.440 / 23.384)×97.18%=0.015%
[0175] Comparison of the calculation results of Example 2 and Example 6, n% TFE and n% PPVE Deviation is 0.02%, unsaturated end group n% 端-总 The deviation is 0.00%.
[0176] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A method for measuring the content of unstable end groups in a fluorinated polymer PFA, comprising: S1. Measure the molar content n% of -CF2-CF2 groups in the sample to be tested TFE ; S2. Using infrared spectroscopy to measure the characteristic absorption peak integral area S of the -CF2-CF2 group in the sample to be tested TFE , and the infrared characteristic absorption peak integral area S of any unstable end group in the sample to be tested 端 Or the sum of the integrated areas of the infrared characteristic absorption peaks of various unstable end groups S 端-总 ; S3. Calculate the molar content n% of any unstable end group in the sample to be tested by the following formula: 端 Or the total molar content of various unstable end groups n% 端-总 : n% 端 =0.0025×(S 端 / S TFE )×n% TFE n% 端-总 =0.0025×(S 端-总 / S TFE )×n% TFE 。 2. The method according to claim 1, characterized in that Step S1 includes: S(1). Measurement of N known TFE monomer molar contents of standard PFA by infrared spectroscopy at (2363±10) cm -1 and (993±10)cm -1 The integrated area of the absorption peak at the wave number A 2363 and A 993 ,get and The relationship curve between and fitting is obtained S(2). Infrared spectroscopy was used to measure the sample at (2363±10)cm -1 The absorption peak integrated area S at the wave number 2363 and (993±10)cm -1 The absorption peak integrated area S at the wave number 993 ; S (3) Calculate the molar content of -CF2-CF2 groups in the sample to be tested by the following formula n% TFE : Among them, n 标 % TFE Indicates the molar content of TFE monomer in standard PFA, n 标 % PPVE Indicates the molar content of PPVE monomer in the standard PFA, K p Indicates that the -O-CF3 group in the standard PFA is at (993±10)cm -1 The sensitivity of K0 represents the -CF2-CF2 group in the standard PFA at (2363±10)cm -1 The sensitivity of the 3. The method according to claim 2, characterized in that N≥3; preferably 4≤N≤10; and / or, In the standard PFA, the molar percentage of TFE monomer is 90-99%; And / or, in the standard PFA, the molar percentage of PPVE monomer is 1-10%.
4. The method according to claim 2 or 3, characterized in that: The value of is 5 to 6, preferably 5.5 to 5.6, and more preferably 5.5603.
5. The method according to any one of claims 1 to 4, characterized in that: In step S2, S TFE The -CF2-CF2 group in the sample to be tested is (2363±10)cm -1 The absorption peak integrated area S at the wave number 2363 .
6. The method according to any one of claims 1 to 5, characterized in that: The unstable end groups include one or more of -COF, -COOH and -CF=CF2; Preferably, S 端 =S -COF , or S 端 =S -COOH , or S 端 =S -COOH Preferably, S 端-总 =S -COF +S -COOH +S -COOH ; Among them, S -COF Indicates that the -COF in the sample to be tested is (1882±10)cm -1 The integrated area of the characteristic absorption peak at the wave number, S -COOH Indicates that -COOH in the sample to be tested is at (1812±10)cm -1 and (1769±10)cm -1 The integrated area of the characteristic absorption peak at the wave number, S -CF=CF2 Indicates that -CF=CF2 in the sample to be tested is at (1793±10)cm -1 The integrated area of the characteristic absorption peak at the wave number.
7. The method according to any one of claims 1 to 6, characterized in that: The method comprises: The sample to be tested was pressed into a tablet and placed in an infrared spectrometer at 400-4000cm -1 Scan within the wave number range to obtain the infrared spectrum; The molar content n% of the -CF2-CF2 group in the sample to be tested is calculated according to the following formula: TFE : The total molar content n% of the unstable end groups in the sample to be tested is calculated according to the following formula 端-总 : Among them, S 2363 It represents (2363±10)cm obtained according to the infrared spectrum. -1 The integrated area of the absorption peak at the wave number; S 993 Indicates (993±10)cm obtained according to the infrared spectrum -1 The integrated area of the absorption peak at the wave number; S 1882 Indicates (1882±10)cm obtained according to the infrared spectrum -1 The integrated area of the absorption peak at the wave number; S 1812 Indicates (1812±10)cm obtained according to the infrared spectrum -1 The integrated area of the absorption peak at the wave number; S 1769 Indicates (1769±10)cm obtained according to the infrared spectrum -1 The integrated area of the absorption peak at the wave number; S 1793 It represents (1793±10)cm obtained according to the infrared spectrum. -1 The integrated area of the absorption peak at that wave number.
8. The method according to claim 7, characterized in that The sample to be tested is in powder or granular form.
9. The method according to claim 8, characterized in that The powdered sample is compressed into tablets through a die at a pressure of 3.5-6.5 MPa; and / or, The granular sample is pressed into a tablet by a hot press at a temperature of 260-300°C, preferably into a tablet with a surface area greater than or equal to 0.25 cm 2 Samples of .
10. The method according to any one of claims 7 to 9, characterized in that: The method further comprises the steps of washing and drying the sample to be tested before tableting. Preferably, the drying temperature is 65-100° C., and the drying time is 2-5 hours.